INCREASING STUDENT INTEREST IN LEARNING SD NEGERI 061/III KEBUN BARU THROUGH THE STUDENT WORK PROGRAM CAMPUS TEACHING 6 - Patmawati, Patmawati (Jurnal Tunas Pendidikan, 2024)
The quality of education in Indonesia is currently still classified as concerning, especially in the 3T area due to the gap in internet access and education. This is also supported by the teaching method of an aducator who is considered boring for students. Therefore, teachers are required to create fun learning. The puspose of this research is to see the students’ interest in learning. In this study, the authors used qualitative research methods. From this research, the results obtained are that there is an increase in students’ interest in learning using various work programs that have been carried out.